Preparation method of spherical alumina-cordierite composite refractory coating composition
The spherical alumina-cordier composite refractory coating composition prepared by co-curing the end amino polymer ultraviolet absorber and spherical alumina-cordier composite material with epoxy resin solves the problem of insufficient UV aging resistance, heat resistance, and fire resistance, and achieves higher impact resistance, thermal stability and waterproof performance.
Patent Information
- Application Number
- CN202510910743.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-08-26
- Estimated Expiration
- 2045-07-02
AI Technical Summary
Traditional epoxy resin coatings have shortcomings in their resistance to UV aging, heat resistance, fire resistance and flame retardant properties.
The end-amino polymer ultraviolet absorber and spherical alumina-cordier composite material are co-cured with epoxy resin to form a spherical alumina-cordier composite refractory coating composition, improving the UV weather resistance, water resistance, heat resistance, and fire resistance of the coating.
The impact resistance, thermal stability and waterproof performance of the paint are significantly improved, while the UV aging resistance and flame retardant properties of the paint are enhanced, and the limit oxygen index is increased to 21.6-24.3%.
Smart Images

Figure BDA0005480021130000021 
Figure BDA0005480021130000031 
Figure BDA0005480021130000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a method for preparing a spherical alumina-cordierite composite refractory coating composition. Background Art
[0002] Epoxy resin coatings offer excellent corrosion resistance and thermal insulation properties, making them widely used. Traditional epoxy resins suffer from poor UV aging resistance, heat resistance, and fire-retardant properties. Alumina, with its high mechanical strength, hardness, and flame retardant properties, is widely used in epoxy resins and other materials. Cordierite, a silicate mineral with excellent fire resistance and low high-temperature expansion, is primarily used in refractory materials. Adding UV absorbers and flame retardants to epoxy resin coatings can improve their UV aging resistance, weather resistance, and fire-retardant properties.
[0003] Traditional UV absorbers for coatings include benzophenones, benzotriazoles, and the like. Chinese patent application CN118580465A discloses a UV-resistant modified epoxy resin and a method for its preparation. The modified epoxy resin prepared using epoxy resin, hydroxyethyl methacrylate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, γ-aminopropyltriethoxysilane, and the like as raw materials has good UV resistance. However, compared to small molecule UV absorbers, macromolecular polymer UV absorbers have better heat resistance, excellent compatibility with polymer resin matrices, and less effect on the mechanical properties of the material. The present invention aims to improve the UV resistance, weather resistance, waterproofness, heat resistance, fire resistance, and flame retardancy of epoxy resin coatings using amino-terminated polymer UV absorbers, alumina, and cordierite. Summary of the Invention
[0004] The technical problem solved by the invention is to improve the anti-ultraviolet and weather-resistant, waterproof, heat-resistant and fire-resistant flame-retardant properties of epoxy resin coating.
[0005] The technical solution of the present invention: a method for preparing a spherical alumina-cordierite composite refractory coating composition:
[0006] Step S1: Add 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole and biphenyldicarboxaldehyde to dimethyl sulfoxide, react in a nitrogen atmosphere, then add 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole, stir and react at 80-110° C. for 12-18 hours, cool, pour the solution into ethanol, filter, wash with ethanol, and dry to obtain an amino-terminated polymer UV absorber. The reaction formula is:
[0007]
[0008] Step S2: 100 parts by weight of epoxy resin, 1-5 parts by weight of amino-terminated polymer UV absorber, 0.5-1 parts by weight of defoamer, 0.4-0.8 parts by weight of leveling agent, 1.2-1.7 parts by weight of dispersant, 15-28 parts by weight of filler, and 29-32 parts by weight of curing agent are stirred and mixed to obtain a spherical alumina-cordierite composite refractory coating composition.
[0009] Preferably, the curing agent is a polyetheramine curing agent.
[0010] Preferably, in step S1, the molar ratio of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole to biphenyldicarboxaldehyde is (1.05-1.1):1.
[0011] Preferably, the preparation method of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole is:
[0012] Step (1) adding 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole, 1,7-bis-BOC-1,4,7-triazaheptane and potassium carbonate to a solvent, stirring at 35-60° C. for 12-24 hours, distilling the solution under reduced pressure, washing with water, and then recrystallizing and purifying in ethanol to obtain a benzotriazole precursor.
[0013] Step (2) Add a benzotriazole precursor to a solution of hydrogen chloride in ethyl acetate, react at room temperature for 4-5 hours, add a sodium bicarbonate solution, shake, and allow to stand for stratification. Remove the lower aqueous phase, dry the upper ethyl acetate extract phase over anhydrous sodium sulfate, filter, and distill the filtrate under reduced pressure. Purify the product by recrystallization in ethanol to obtain 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole. The reaction formula is:
[0014]
[0015] Preferably, the solvent in step (1) is any one or a combination of acetonitrile, tetrahydrofuran, and water.
[0016] Preferably, in step (1), the molar ratio of 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole, 1,7-bis-BOC-1,4,7-triazaheptane, and potassium carbonate is (1.1-1.3):1:(1.1-1.5).
[0017] The technical effect of the present invention is as follows: the present invention adds an amino-terminated polymer UV absorber to the epoxy resin coating, which contains an amino group and can replace part of the polyetheramine curing agent, undergo a co-curing reaction with the epoxy resin, improve the curing and cross-linking properties of the epoxy resin, avoid affecting the mechanical properties of the coating film due to insufficient addition of the curing agent, and make the coating film have higher impact resistance.
[0018] The polymer UV absorber of the present invention contains o-hydroxybenzotriazole groups, which can convert ultraviolet light energy into chemical energy and thermal energy, thereby improving the ultraviolet absorption characteristics of the paint film and showing excellent anti-ultraviolet aging performance.
[0019] The UV absorber of the present invention is a heat-resistant macromolecular polymer with a thermally stable biphenyl structure in its molecular backbone. Co-curing with an epoxy resin improves the heat resistance of the paint film, resulting in a higher thermal decomposition temperature. Co-curing with the epoxy resin results in tight crosslinking of the epoxy resin molecular chains. Furthermore, the hydrophobic biphenyl structure inhibits the ingress of water molecules into the paint film, thereby improving water and water resistance. This UV absorber has promising practical applications in weather-resistant, fire-resistant, and waterproof coatings.
[0020] The limiting oxygen index of traditional epoxy resins and their coatings is only about 18%. The present invention adds spherical alumina trihydrate and cordierite to the coating. The spherical alumina trihydrate can have flame retardant and smoke suppression effects, and the cordierite has high fire resistance and low high-temperature expansion rate. The combination of the two increases the limiting oxygen index of the coating to 21.6-24.3%, thereby improving the flame retardant and fire resistance of the coating. DETAILED DESCRIPTION
[0021] To make the objectives, technical solutions, and advantages of the present invention more apparent, the technical solutions of the present invention will be described in detail below. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other implementations obtained by those of ordinary skill in the art without inventive effort are within the scope of protection of the present invention.
[0022] 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole was prepared according to the method of the document "Synthesis of Reactive Chloroacetylbenzotriazole UV Absorber" in the journal "Company of Surfactant", Vol. 39, No. 3, June 2009. The structural formula is
[0023] Example 1:
[0024] (1) To 25 mL of tetrahydrofuran and 10 mL of water were added 26 mmol of 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole, 20 mmol of 1,7-bis-BOC-1,4,7-triazaheptane, and 30 mmol of potassium carbonate. The mixture was stirred at 35°C for 24 h. The solution was distilled under reduced pressure, washed with water, and then purified by recrystallization from ethanol to obtain a benzotriazole precursor.
[0025] (2) 3 g of benzotriazole precursor was added to 30 mL of 1 mol / L hydrogen chloride in ethyl acetate solution, and the mixture was reacted at room temperature for 4 h. Sodium bicarbonate solution was added, and the mixture was allowed to stand for stratification after shaking. The lower aqueous phase was removed, and the upper ethyl acetate extract phase was dried over anhydrous sodium sulfate. After filtration, the filtrate was distilled under reduced pressure, and the product was purified by recrystallization in ethanol to obtain 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole.
[0026] (3) 10 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole and 10 mmol of biphenyldicarboxaldehyde were added to 50 mL of dimethyl sulfoxide and reacted in a nitrogen atmosphere. 0.5 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole was then added and stirred at 90°C for 18 h. After cooling, the solution was poured into ethanol, filtered, washed with ethanol, and dried to obtain an amino-terminated polymer UV absorber.
[0027] (4) Add 100 g of epoxy resin E51, 1 g of terminal amino polymer UV absorber, 0.5 g of defoaming agent ECO-A860, 0.7 g of leveling agent, 1.2 g of dispersant, 11 g of spherical alumina trihydrate, 4 g of cordierite, and 32 g of polyetheramine D230 curing agent to 130 mL of toluene solvent, stir and mix to obtain a spherical alumina-cordierite composite refractory coating composition.
[0028] Example 2:
[0029] (1) To 30 mL of acetonitrile were added 22 mmol of 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole, 20 mmol of 1,7-bis-BOC-1,4,7-triazaheptane, and 22 mmol of potassium carbonate. The mixture was stirred at 60°C for 12 h. The solution was distilled under reduced pressure, washed with water, and then recrystallized from ethanol to obtain a benzotriazole precursor.
[0030] (2) 3 g of benzotriazole precursor was added to 25 mL of 1 mol / L hydrogen chloride in ethyl acetate solution, and the mixture was reacted at room temperature for 5 h. Sodium bicarbonate solution was added, and the mixture was allowed to stand for stratification after shaking. The lower aqueous phase was removed, and the upper ethyl acetate extract phase was dried over anhydrous sodium sulfate. After filtration, the filtrate was distilled under reduced pressure, and the product was purified by recrystallization from ethanol to obtain 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole.
[0031] (3) 10 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole and 10 mmol of biphenyldicarboxaldehyde were added to 60 mL of dimethyl sulfoxide and reacted in a nitrogen atmosphere. 1 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole was then added and stirred at 110°C for 12 h. After cooling, the solution was poured into ethanol, filtered, washed with ethanol, and dried to obtain an amino-terminated polymer UV absorber.
[0032] (4) Add 100 g of epoxy resin E51, 2 g of terminal amino polymer UV absorber, 1 g of defoaming agent ECO-A860, 0.4 g of leveling agent, 1.7 g of dispersant, 14 g of spherical alumina trihydrate, 6 g of cordierite, and 31 g of polyetheramine D230 curing agent to 130 mL of toluene solvent, stir and mix, and obtain a spherical alumina-cordierite composite refractory coating composition.
[0033] Example 3:
[0034] (1) To 60 mL of dimethyl sulfoxide were added 10 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole (prepared according to the method of Example 1) and 10 mmol of biphenyldicarboxaldehyde, and the mixture was reacted in a nitrogen atmosphere. 0.8 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole was then added, and the mixture was stirred at 80° C. for 18 h. After cooling, the solution was poured into ethanol, filtered, washed with ethanol, and dried to obtain an amino-terminated polymer UV absorber.
[0035] (2) Add 100 g of epoxy resin E51, 3.5 g of terminal amino polymer UV absorber, 0.5 g of defoaming agent ECO-A860, 0.8 g of leveling agent, 1.2 g of dispersant, 16 g of spherical alumina trihydrate, 8 g of cordierite, and 30 g of polyetheramine D230 curing agent to 130 mL of toluene solvent, stir and mix to obtain a spherical alumina-cordierite composite refractory coating composition.
[0036] Example 4:
[0037] (1) To 60 mL of dimethyl sulfoxide were added 10 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole (prepared according to the method of Example 1) and 10 mmol of biphenyldicarboxaldehyde, and the mixture was reacted in a nitrogen atmosphere. 0.5 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole was then added, and the mixture was stirred at 110° C. for 12 h. After cooling, the solution was poured into ethanol, filtered, washed with ethanol, and dried to obtain an amino-terminated polymer UV absorber.
[0038] (2) Add 100 g of epoxy resin E51, 5 g of terminal amino polymer UV absorber, 1 g of defoaming agent ECO-A860, 0.6 g of leveling agent, 1.2 g of dispersant, 18.5 g of spherical alumina trihydrate, 9.5 g of cordierite, and 29 g of polyetheramine D230 curing agent to 130 mL of toluene solvent, stir and mix to obtain a spherical alumina-cordierite composite refractory coating composition.
[0039] Comparative Example 1:
[0040] (1) 100 g of epoxy resin E51, 0.5 g of defoaming agent ECO-A860, 0.7 g of leveling agent, 1.2 g of dispersant, 11 g of spherical alumina trihydrate, 4 g of cordierite, and 32 g of polyetheramine D230 curing agent were added to 130 mL of toluene solvent and stirred to obtain a coating composition.
[0041] Comparative Example 2:
[0042] (1) 100 g of epoxy resin E51, 1 g of 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole, 0.5 g of defoamer ECO-A860, 0.7 g of leveling agent, 1.2 g of dispersant, 11 g of spherical alumina trihydrate, 4 g of cordierite, and 32 g of polyetheramine D230 curing agent were added to 130 mL of toluene solvent and stirred to obtain a coating composition.
[0043] Comparative Example 3:
[0044] (1) 100 g of epoxy resin E51, 1 g of benzotriazole precursor, 0.5 g of defoaming agent ECO-A860, 0.7 g of leveling agent, 1.2 g of dispersant, 11 g of spherical alumina trihydrate, 4 g of cordierite, and 32 g of polyetheramine D230 curing agent were added to 130 mL of toluene solvent and stirred to obtain a coating composition.
[0045] Comparative Example 4:
[0046] (1) To 50 mL of dimethyl sulfoxide were added 10 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole (prepared according to the method of Example 1) and 10 mmol of glutaraldehyde, and the reaction was carried out in a nitrogen atmosphere. 0.5 mmol of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole was then added, and the mixture was stirred at 90° C. for 18 h. After cooling, the solution was poured into ethanol, filtered, washed with ethanol, and dried to obtain an amino-terminated polymer UV absorber.
[0047] (2) 100 g of epoxy resin E51, 1 g of amino-terminated polymer UV absorber, 0.5 g of defoamer ECO-A860, 0.7 g of leveling agent, 1.2 g of dispersant, 11 g of spherical alumina trihydrate, 4 g of cordierite, and 32 g of polyetheramine D230 curing agent were added to 130 mL of toluene solvent and stirred to obtain a coating composition.
[0048] The coating was applied to the tinplate surface and cured at 80°C for 1 hour, 100°C for 3 hours, and 130°C for 30 minutes. The impact resistance of the paint film was tested according to GB / T 1732-2020.
[0049] 10 mg of the paint film was weighed and placed in a thermogravimetric analyzer for thermogravimetric performance analysis in a nitrogen atmosphere, with the temperature rising from room temperature to 700°C at a heating rate of 10°C / min.
[0050] Water resistance is tested according to GB / T 1733-1993.
[0051] The paint film was subjected to a UV aging test at a total power of 240W and a central wavelength of 365nm. The test temperature was 55°C and the UV aging time was 14 days. The surface condition of the paint film was observed after UV aging.
[0052] The oxygen index and fire retardant properties are tested according to GB / T 2406.1-2008 standard.
[0053] Table 1
[0054]
[0055]
[0056] T 5% T is the temperature at which the thermogravimetric loss is 5%. max is the temperature at which the thermal decomposition rate is maximum.
[0057] After testing, compared with comparative example 1, the epoxy resin coatings of examples 1-4 have higher impact resistance, T 5% and T maxTemperature, mechanical properties and heat resistance are better, and water resistance, waterproofness, UV aging resistance are excellent, and it shows excellent weather resistance. This is mainly because the amino-terminated polymer UV absorber is added. It contains amino groups and can replace part of the polyetheramine curing agent, and undergoes a co-curing reaction with the epoxy resin to improve the curing and cross-linking properties of the epoxy resin, avoiding the mechanical properties of the paint film affected by insufficient curing agent addition, and making the paint film have higher impact resistance. At the same time, the UV absorber is a macromolecular polymer, and its heat resistance is higher than that of small molecule UV absorbers. At the same time, the molecular main chain of the polymer UV absorber contains a thermally stable biphenyl structure, which is beneficial to improve the heat resistance after co-curing with the epoxy resin, showing a higher T 5% and T max Temperature. Furthermore, after co-curing with the epoxy resin, the amino-terminated polymer UV absorber tightly crosslinks the epoxy resin molecular chains. Its hydrophobic biphenyl structure inhibits water molecules from entering the paint film, thereby improving water resistance. The polymer UV absorber contains o-hydroxybenzotriazole groups, which convert UV energy into chemical and thermal energy, thereby enhancing the UV absorption properties of the paint film and demonstrating excellent resistance to UV aging.
[0058] The 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole added in Comparative Example 2 does not contain an amino group and cannot undergo a curing reaction with the epoxy resin. It has poor compatibility with the epoxy resin and will affect the impact resistance and mechanical properties of the paint film. Moreover, as a small molecule compound, it has poor heat resistance, which leads to the T 5% and T max The temperature is low and the water resistance is poor.
[0059] The benzotriazole precursor added in Comparative Example 3 contains amino groups, which can react with epoxy resin to cure the epoxy resin, so that the epoxy resin maintains good impact resistance and mechanical properties. 5% and T max The temperature is low and the water resistance is poor.
[0060] Comparative Example 4: Glutaraldehyde and benzotriazole precursor were used to carry out polymerization reaction. The obtained polymer as absorbent did not contain thermally stable and hydrophobic biphenyl structure, resulting in the T 5% and T max The temperature is low and the water resistance is poor.
[0061] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.
Claims
1. A method for preparing a spherical alumina-cordierite composite refractory coating composition, characterized in that: The preparation method is: Step S1, adding 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole and biphenyldicarboxaldehyde to dimethyl sulfoxide, reacting in a nitrogen atmosphere, then adding 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole, reacting, cooling, pouring the solution into ethanol, filtering, washing, and drying to obtain an amino-terminated polymer UV absorber; Step S2, stirring and mixing 100 parts by weight of epoxy resin, 1-5 parts by weight of amino-terminated polymer UV absorber, 0.5-1 parts by weight of defoamer, 0.4-0.8 parts by weight of leveling agent, 1.2-1.7 parts by weight of dispersant, 15-28 parts by weight of filler, and 29-32 parts by weight of curing agent to obtain a spherical alumina-cordierite composite refractory coating composition; The filler includes any one of spherical alumina trihydrate and cordierite or a combination thereof.
2. The method for preparing the spherical alumina-cordierite composite refractory coating composition according to claim 1, characterized in that: The reaction in step S1 is carried out at 80-110° C. for 12-18 hours.
3. The method for preparing the spherical alumina-cordierite composite refractory coating composition according to claim 1, wherein: In step S1, the molar ratio of 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole to biphenyldicarboxaldehyde is (1.05-1.1):
1.
4. The method for preparing the spherical alumina-cordierite composite refractory coating composition according to claim 3, characterized in that: The preparation method of the 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole is as follows: Step (1) adding 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole, 1,7-bis-BOC-1,4,7-triazaheptane, and potassium carbonate to a solvent, and after the reaction, distilling the solution under reduced pressure, washing, and recrystallizing and purifying to obtain a benzotriazole precursor; Step (2) adding a benzotriazole precursor to a solution of hydrogen chloride in ethyl acetate, reacting at room temperature for 4-5 hours, extracting and separating after the reaction, and purifying by recrystallization to obtain 2-[2'-hydroxy-3'-(diethylenetriamine)acetyl-5'-methylphenyl]benzotriazole.
5. The method for preparing the spherical alumina-cordierite composite refractory coating composition according to claim 4, characterized in that: The solvent in step (1) is any one or a combination of acetonitrile, tetrahydrofuran and water.
6. The method for preparing the spherical alumina-cordierite composite refractory coating composition according to claim 4, wherein: In the step (1), the molar ratio of 2-(2'-hydroxy-3'-chloroacetyl-5'-methylphenyl)benzotriazole, 1,7-bis-BOC-1,4,7-triazaheptane, and potassium carbonate is (1.1-1.3):1:(1.1-1.5).
7. The method for preparing the spherical alumina-cordierite composite refractory coating composition according to claim 4, characterized in that: The reaction in step (1) is carried out at 35-60° C. for 12-24 hours.
8. The method for preparing the spherical alumina-cordierite composite refractory coating composition according to claim 1, characterized in that: The curing agent in step S2 is a polyetheramine curing agent.
Citation Information
Patent Citations
Modified carbon nanotube-fluorocarbon resin and application thereof in wear-resistant aluminum veneer
CN115491089A
Preparation process and application of hyperbranched polyether surfactant
CN116355196A
Preparation method of porous adsorption resin for treating high-salt high-ammonia-nitrogen wastewater and metal wastewater
CN118420812A
Anti-ultraviolet modified epoxy resin and preparation method thereof
CN118580465A
Herbicides containing substituted thien-3-yl-sulfonylamino(thio)carbonyl-triazolin(thi)one compound
CN1589101A